LEARNING IMPLEMENTATION USING TPACK WITH SCIENTIFIC APPROACH ASSISTED BY E-MODUL PAI - Moh. Nawafil; Luluk Maktumah; Junaidi Junaidi; Moh. Hafid (Fakultas Tarbiyah, Universitas Ibrahimy, 2025)
This study aims to analyze the differences in learning outcomes between students who apply scientific TPACK learning assisted by PAI (Islamic Religious Education) e-modules and students who apply scientific TPACK learning in grade IX on the subject of Islam's presence in reconciling the Indonesian archipelago. A quantitative approach with a quasi-experimental research design was used in this study. Data collection utilized testing techniques and observation techniques. The data analyzed were quantitative data obtained from pretest and posttest learning outcomes of students in the experimental and control groups. Based on the research results, at a significance level of 5% and a sig. (two-tailed) of 0,000, it was found that students who participated in TPACK learning using a scientific approach assisted by PAI e-modules in the ninth grade of junior high school achieved significantly higher learning outcomes than students who only participated in TPACK learning using a scientific approach. These results are also supported by previous studies that confirm the effectiveness of digital teaching materials in improving the quality of learning. Through this research, it is also proven that PAI learning, which was previously textual and abstract, resulting in a decline in student learning outcomes, has now become more concrete, interactive, and applicable, and has successfully improved student learning outcomes through the use of emodules.